A systematic review of clinical guidelines on choice, dose, and duration of antipsychotics treatment in first- and multi-episode schizophrenia. (18th August 2019) - Hui, Christy L. M.; Lam, Bertha S. T.; Lee, Edwin H. M.; Chan, Sherry K. W.; Chang, Wing C.; Suen, Y. N.; Chen, Eric Y. H.
Abstract: Clinical guidelines provide evidence-based recommendations to regulate pharmacological treatment of psychotic disorders. However, the quality of evidence, country of origin, and publication dates of such guidelines vary, which leads to discrepancies between recommendations. This systematic review aimed to examine consensus and disparities between clinical recommendations on the choice, dose, and duration of antipsychotic treatment for first- and multi-episode schizophrenia patients. A literature search through The Cochrane Library, Embase, Medline, PsycINFO, PubMed, Scopus, Web of Sciences, and relevant bibliographies revealed 24 guidelines that met the inclusion criteria. The guidelines indicated mostly consistent recommendations regarding the optimal dose range of antipsychotics, while guidance with regards to the choice and duration of treatment remains somewhat controversial. Current trends in guidelines emphasize that there is simply no 'one-size-fits-all' method to manage schizophrenia patients. Further research is needed not only to address discrepancies between guidelines, but also to justify the gap between theory and practice.